KAJIAN LAPANGAN PERKERASAN JALAN BETON PRACETAK DI INDONESIA - A. Tatang Dachlan (Jurnal Jalan-Jembatan, 2009)
To improve the application of the precast concrete pavement more efficient and ensure well quality, Research and Development Centre For Road and Bridge (RDCRB) has studied the development of precast cement concrete in several agencies of some developed countries, and performs monitoring of precas concrete pavement in Indonesia such asat Busway lane and Cakung-Cilincing road link in Jakarta, and toll road link at Kanci-Pejagan, Cirebon, West Java. To find out the performance, visual surface pavement condition survey, vertical deflection measurement and road roughness survey were carried out. The result shows that in the first year the pavement proved relatively strong to support heavy traffic load, although at some joints and edges of panels have surface and edge defects that caused significantly high deflection and roughness. Surface roughness arround 2,3 m/Km at Kanci-Pejagan is relatively good. RDCRB have studied small scale in the laboratory using two joints variations. The performance of joints is then examined to vertical and horizontal deformation, and the result shows safe deformation. The evaluation result will be applied on the field trials of precast concrete by RDCRB. Keywords: precats concrete, prestress, precast-prestress, panel, vertical deflection